2006
DOI: 10.1186/1476-9255-3-16
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background: The inflammatory response to hepatic ischemia-reperfusion (I/R) is associated with an increase in cytokine production. Studies have documented that sex hormones modulate both the innate and adaptive immune responses, and that females are more robust than males. The aim of this study was to determine whether a sex difference in cytokine response to hepatic I/R exists under normal pathophysiologic condition without hormone intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 36 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…We used only male C57BL/6 N mice for this primary study because gender of mice affects hormones and cell-mediated immune response [ 20 , 21 ]. Cytokine expression also differs between male and female mice [ 22 ]. Further studies with female mice will be necessary.…”
Section: Methodsmentioning
confidence: 99%
“…We used only male C57BL/6 N mice for this primary study because gender of mice affects hormones and cell-mediated immune response [ 20 , 21 ]. Cytokine expression also differs between male and female mice [ 22 ]. Further studies with female mice will be necessary.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we observed greater dysbiosis of the transcriptome in ApoE4-KI males. There are several studies that have demonstrated evidence of sex differences in the expression of DPGs and inflammation genes 67 69 . For example, a 2011 study showed that the release of growth hormone was associated with the difference in the expression of sulfotransferases between sexes 70 .…”
Section: Discussionmentioning
confidence: 99%
“…Sex-based differences in IR have been noted by others in patients with cardiac, renal, and liver injury [ 26 30 ]. Our study showed sex-based differences in the clinical phenotype of IR injury (PGD), as well as IR-induced cytokine production, after lung transplantation.…”
Section: Discussionmentioning
confidence: 90%